2004
DOI: 10.1002/neu.10308
|View full text |Cite
|
Sign up to set email alerts
|

Novel changes in gene expression following axotomy of a sympathetic ganglion: A microarray analysis

Abstract: Neurons of the peripheral nervous system are capable of extensive regeneration following axonal injury. This regenerative response is accompanied by changes in gene expression in axotomized neurons and associated nonneuronal cells. In the sympathetic nervous system, a few of the genes affected by axonal injury have been identified; however, a broad sampling of genes that could reveal additional and unexpected changes in expression has been lacking. We have used DNA microarray technology to study changes in gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
88
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 66 publications
(74 reference statements)
2
88
0
Order By: Relevance
“…However, PACAP expression increases markedly in these neurons following axotomy or explant culture (Zhang et al, 1995(Zhang et al, ,1996Moller et al, 1997a,b;Zhou et al, 1999;Pettersson et al, 2004). It is hypothesized that the increased expression of PACAP may be a response to injury that supports cell survival and regeneration (Moller et al, 1997a,b;Armstrong et al, 2003;Boeshore et al, 2004;Pettersson et al, 2004;Suarez et al, 2006).…”
Section: Author Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations
“…However, PACAP expression increases markedly in these neurons following axotomy or explant culture (Zhang et al, 1995(Zhang et al, ,1996Moller et al, 1997a,b;Zhou et al, 1999;Pettersson et al, 2004). It is hypothesized that the increased expression of PACAP may be a response to injury that supports cell survival and regeneration (Moller et al, 1997a,b;Armstrong et al, 2003;Boeshore et al, 2004;Pettersson et al, 2004;Suarez et al, 2006).…”
Section: Author Manuscriptmentioning
confidence: 99%
“…In rat SCG neurons, one key mechanism stimulating a change in transmitter phenotype in ganglia explants or after axotomy is the production and secretion of a regulatory factor, leukemia inhibitory factor (LIF), by non-neural cells (Sun et al, 1994;Lewis et al, 1994;Sun and Zigmond, 1996;Cheng et al, 1997;Boeshore et al, 2004). Consequently, we tested, using an immunocytochemical assay, whether members of a number of common regulatory factor and/or target-derived factor families enhanced PACAP expression.…”
Section: Members Of Common Regulatory Factor Families Do Not Stimulatmentioning
confidence: 99%
See 2 more Smart Citations
“…Tsujino and colleagues (2000) identified activating transcription factor 3 (ATF3) as a gene that is expressed in both sensory and motor neurons after sciatic nerve injury while being undetectable in these same neurons in the intact animal. Similarly, we have recently found that, while ATF3 is not normally expressed in sympathetic neurons in the superior cervical ganglion (SCG), it is expressed in these neurons after transection of the postganglionic internal and external carotid nerves (Boeshore et al, 2004;Hyatt-Sachs, Schreiber, Shoemaker, Sabe, Reed, and Zigmond submitted). While ATF3 has been proposed as a marker for injured neurons (Tsujino et al, 2000), in a study on the corticospinal tract after axotomy, Mason et al (2003) found that the expression of ATF3 increased following a proximal lesion (i.e., a lesion 350-500 μm from the cell soma), but not following a more distal lesion.…”
Section: Introductionmentioning
confidence: 87%